Biochemical and antidiabetic properties of Elaeocarpus angustifolius Blume: In vitro, In vivo, and In silico insights - Sabina Panth; Rojina Devkota; Amar Waiba; Tika Ram Lamichhane; Prajwal Acharya; Begum Rokeya; Amit Jaisi; Achyut Adhikari (PLoS ONE, 2026)
Diabetes poses an utmost threat to human health; significant progress in the discovery of antidiabetic drugs has been made, but their side effects cannot be ignored. As a plant-based alternative, this study explored the pharmacological potential of Elaeocarpus angustifolius Blume (Rudraksha), emphasizing its antioxidant and antidiabetic activities, supported by in silico analysis. Phytochemical screening of the methanol bark extract confirmed the presence of flavonoids, alkaloids, carbohydrates, glycosides, terpenoids, tannins, and phenols. The extract exhibited high total phenolic and flavonoid contents (182.73 ± 0.001 mg GAE/g and 48.78 ± 0.06 mg QE/g, respectively). The LC–MS analysis of the ethyl acetate fraction identified thirteen phytoconstituents, including phenolic acids, flavonoids, and tannins. The ethyl acetate fraction demonstrated significant antioxidant activity (IC₅₀ = 1.47 ± 0.37 µg/mL), outperforming quercetin (IC₅₀ = 4.87 ± 0.16 µg/mL). Enzyme inhibition assays revealed methanol extract has strong α-glucosidase (IC₅₀ = 0.79 ± 0.13 µg/mL) and α-amylase (IC₅₀ = 3.48 ± 0.00 µg/mL) inhibitory effects, comparable to acarbose (IC₅₀ = 13.51 ± 0.22 µg/mL and IC₅₀ = 25.30 ± 0.85 µg/mL), respectively. In a 28-day in vivo study, oral administration of the methanol bark extract significantly (p < 0.01) reduced fasting serum glucose levels and improved lipid profiles, with decreases in triglycerides (5%) and total cholesterol (2%), and an increase in HDL (5%) compared with baseline. The extract-treated group also showed higher hepatic glycogen content (14.06 ± 0.002 mg/mL) than the Gliclazide-treated group (12.82 ± 0.002 mg/mL). In silico molecular docking identified Corilagin exhibiting the highest binding affinity (−10.3 kcal/mol), stable interaction (RMSD = 1.469 ± 0.133 Å), and favorable binding free energy (ΔG BFE = −27.48 ± 3.15) with α-amylase, suggesting that it may act as a competitive inhibitor of an enzyme’s active site. Overall, these findings highlight that E. angustifolius bark significantly inhibits glucose absorption and improves dyslipidemia to some extent, while in silico analysis suggests that Corilagin has potential as an inhibitory activity against type-2 diabetes.